Violence and politics : ideologies, identities, representations - Ampoutis, Antonios; Dimitriadis, Marios; Dimitriadis, Sakis; Konstantellou, Theodora; Mamali, Maria; Saraphēs, Vangelēs, 1989- (Cambridge Scholars Publishing, 2018)
In this volume, a new generation of researchers explore and demonstrate the interaction between politics and violence in the context of Greek and European history. In terms of focus, the articles here extend over a time span stretching from the Greek classical period to the twentieth century. The ancient Greek polis, medieval and early modern Europe, Byzantium and the Ottoman Empire, nineteenth-century Britain and the Greek society of the 1940s are some of the historical periods in which the relationship between violence and politics is examined. At the same time, the authors tackle important themes concerning this relationship, such as legitimate and illegitimate violence, violence from above and from below, resistance and revolt, authority and subordination, and gendered and political violence--back cover.